2018
DOI: 10.1097/md.0000000000010128
|View full text |Cite
|
Sign up to set email alerts
|

The expression of HtrA2 and its diagnostic value in patients with hepatocellular carcinoma

Abstract: The purpose of this study was to detect the expression of high-temperature requirement A2 (HtrA2) and its diagnostic value in the patients with hepatocellular carcinoma (HCC).The relative serum HtrA2 expression at mRNA and protein level was severally detected by quantitative real-time polymerase chain reaction and western blot analysis in 198 HCC patients and 48 healthy controls. And its association with clinicopathological features was analyzed by chi-square test. The diagnostic value of HtrA2 expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The investigators indicated that HTRA2, served as an oncogene, is significantly correlated with tumor size and clinical stage. That is, patients with high expression of HTRA2 are more likely to develop large tumors and progress to clinically advanced stages, which is consistent with the ROC curves that suggest HTRA2 is highly diagnostic for cancer 118 . By contrast, lower expression of HTRA2 in some cancer tissues than their normal counterparts suggests the cancer‐suppressive effect of HTRA2 (Figure 6).…”
Section: Protein Quality Control In the Mitochondria Of Cancerssupporting
confidence: 79%
See 1 more Smart Citation
“…The investigators indicated that HTRA2, served as an oncogene, is significantly correlated with tumor size and clinical stage. That is, patients with high expression of HTRA2 are more likely to develop large tumors and progress to clinically advanced stages, which is consistent with the ROC curves that suggest HTRA2 is highly diagnostic for cancer 118 . By contrast, lower expression of HTRA2 in some cancer tissues than their normal counterparts suggests the cancer‐suppressive effect of HTRA2 (Figure 6).…”
Section: Protein Quality Control In the Mitochondria Of Cancerssupporting
confidence: 79%
“…That is, patients with high expression of HTRA2 are more likely to develop large tumors and progress to clinically advanced stages, which is consistent with the ROC curves that suggest HTRA2 is highly diagnostic for cancer. 118 By contrast, lower expression of HTRA2 in some cancer tissues than their normal counterparts suggests the cancer-suppressive effect of HTRA2 (Figure 6). The analysis for 65 colorectal cancer patients conducted by Dorota et al verified that HTRA2 mRNA and protein levels are obviously lower in cancerous tissues than in normal colorectal mucosa, especially in patients with metastatic colorectal cancer.…”
Section: Htra2mentioning
confidence: 98%
“…According to the results of previous studies, higher expression of HtrA2 had been found in malignant thyroid tumors, gastric cancer, and prostate cancer, and it was predictive of poor patient outcomes [ 27 30 ]. However, the expression of HtrA2 was found to be very low, which predicted poor outcomes in non-small-cell lung cancer and ovarian cancer [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…HtrA2 is localized to the mitochondrial intermembrane space and can in uence the physiology of mitochondrial homeostasis [8, 9,17]. Its aberrant expression has been linked to a variety of illnesses, including ovarian cancer, endometrial cancer, as well as neurological disorders [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…It is an apoptosis-inducing protein that is released after an apoptotic stimulus from the mitochondrial intermembrane space into the cytosol [8]. HtrA2 has roles in the progression of neurodegenerative diseases, prostate cancer, and hepatocellular carcinoma [8,9]. However, HtrA2 controls in ammation and immune response remains unknown.…”
Section: Introductionmentioning
confidence: 99%